Labor market dynamics when (un)employment is a social norm - Koursaros, Demetris (My University, 2017)
This paper proposes a new Keynesian model with search and matching frictions in the labor market that can account for the cyclicality and persistence of vacancies, unemployment, job creation, inflation and the real wage, after a monetary shock. Motivated by evidence from psychology, unemployment is modeled as a social norm. The norm is defined here as the belief that individuals in society prioritize, or should prioritize the search for gainful employment, whereas those who do not are perceived as outside the norm and, consequently, stigmatized. Households pressure the unemployed to find jobs: the fewer unemployed workers there are, the more supporters the norm has and therefore the greater the pressure and psychological cost experienced by each jobseeker. As this psychological cost is procyclical, it hinders the wage from absorbing most of the effect of the shock. Thus, the model is able to capture the high volatility of vacancies and unemployment observed in the data, accounting for the Shimer puzzle. The paper also departs from the literature by introducing price rigidity in the labor market, inducing additional inertia and persistence in inflation and the real wage after a monetary shock. The model's responses after a monetary shock are in line with the responses obtained from a VAR on US data.
Keywords: DSGE; Psychological cost of unemployment; Unemployment; Vacancies; Social norm